Strategi Kepala Madrasah dalam Meningkatkan Akhlak Mulia Peserta Didik di Madrasah Aliyah Darul Ulum Ngabar Jetis Mojokerto - M. Iqbaluddin Al Huda; Barnoto Barnoto (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This research is a qualitative research with a case study approach. There are two types of secondary and primary data to support this research. Data collection techniques using observation, interviews and documentation. The data analysis techniques use data collection, reduction, data presentation, and drawing conclusions. Meanwhile, to test the credibility of this study using triangulation. The results of the study show that 1) The principal's strategy in improving the noble character of students is by instilling religious values, doing good things, and always giving advice. 2) Noble morals of students, namely morals to Allah including the discipline of carrying out midday and midday prayers in congregation, fond of giving alms and morals to others is the discipline of adhering to school rules, having a caring and responsible soul. 3) The inhibiting factors are the lack of understanding of noble character, the lack of time to instill religious values, and association outside of school. While the supporting factors include the support of the madrasah head, good cooperation with fellow teachers, adequate infrastructure, parental support, and a good environment outside the school.